Analisis Faktor Ibu Dengan Kejadian Memiliki Anak Balita Stunting Di Kota Pekanbaru - Elly Satriani Harahap; Tri Krianto Karjoso; Reli Sugianti (STIKes Payung Negeri Pekanbaru, 2019)
Stunting is a condition of growing failure from children under five (infants under five years) which results in children being too short for their age as a result of chronic malnutrition. In Pekanbaru City from Nutritional Status Monitoring data in 3 (three) consecutive years, the prevalence of stunting was increased by 17.7%, 23.9%, and 27.7%. The aim is to analyze how the relationship between maternal factors is the cause of the occurrence of having stunting children in the Harapan Raya City Health Center in Pekanbaru in 2019. This research is a quantitative research with cross sectional design and sharpened with qualitative research with case study designs in the Harapan Raya Community Health Center working area in June 2019 with a sample of 187 toddlers and sample selection by purposive sampling. Data collection using questionnaires, interview guidelines, and observation lists. Based on the study of the frequency of occurrence of having a stunting toddler is 52.4% and a multivariate analysis with a multiple factor predictive logistic regression test concludes the Hb value of Mother in Pregnancy (p value = 0.002), Maternal Behavior in Parenting Feeding Patterns (p value = 0.016 ), and Exclusive breastfeeding (p value = 0.001) is an independent variable that is significantly related to the risk of occurrence of having a stunting toddler and a confounding variable on the risk of having a stunting toddler namely child distance and maternal parity. For Puskesmas, it is expected to provide information regarding stunting issues in the working area of ​​Harapan Raya Health Center by conducting cross-program collaboration in KIA, GIZI, and Promkes. Keywords : Stunting Toddler Children, Mother Hb Value, Exclusive Breastfeeding, Toddler Child Feeding Behavior, Harapan Raya Health Center Working